2023
DOI: 10.7759/cureus.41650
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Images and Contrast-Enhanced MRI in the Diagnosis of Different Stages of Multiple Sclerosis of the Central Nervous System

Abstract: IntroductionMultiple sclerosis (MS) is one of the most prevalent disorders of the central nervous system (CNS), and it can be observed in the field of radiological cross-sectional magnetic resonance imaging (MRI). The prevalence of MS in Saudi Arabia has increased as compared to the past few years. MRI is the gold standard non-invasive modality of choice in MS diagnosis according to the National Multiple Sclerosis Society (NMSS), New York City. This study aimed to highlight the significance of using diffusion-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…However, Heydarpour et al's systematic study and meta-analysis of MS epidemiology revealed that the most common symptom among Saudi MS patients was weakness [20]. These outcomes support those of a cross-sectional study conducted in KSA by AlJumah et al; the researchers discovered that, of the 2516 MS cases, muscle weakness was the most common symptom at the onset (57.1%), followed by visual symptoms (48.2%) [21].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, Heydarpour et al's systematic study and meta-analysis of MS epidemiology revealed that the most common symptom among Saudi MS patients was weakness [20]. These outcomes support those of a cross-sectional study conducted in KSA by AlJumah et al; the researchers discovered that, of the 2516 MS cases, muscle weakness was the most common symptom at the onset (57.1%), followed by visual symptoms (48.2%) [21].…”
Section: Introductionmentioning
confidence: 74%
“…Overall, very little research has been conducted with Saudi MS patients and most studies that have been carried out focus on EDSS scores or symptoms related to MS. None of those studies examined spinal cord changes in patients with MS using MRI. In addition, MS is now more common in KSA than it was just a few years ago [19,21]. In 2015, KSA launched its first national MS registry involving multiple centers; it now has 20 participating hospitals.…”
Section: Introductionmentioning
confidence: 99%